Augmented Reality Trasnportasi Darat Menggunakan FAST Corner Detection dan Lucas Kanade - Andre Tegar Pratama (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
The digital age makes learning media more diverse, if previously using print media, then now using all electronics, such as e-books and learning applications. One of the technologies that can be used as a learning medium with the form of objects in real-time known as Augmented Reality (AR). The design of this AR application aims to introduce land transportation to early childhood. The study was developed using the Single Marker method as well as the FAST Corner Detection and Lucas Kanade algorithms. Land transportation that became the case in this study is bicycles, motorcycles, rickshaws, rickshaws, cars, buses, trucks, and trains. Information about land transportation in this AR application can attract children to know more about the various vehicles that can be used. The results of the Realme XT device research showed the accuracy level in AR can best be detected with maximum distance range with the best distance, the best angle to read on, and Realme XT light intensity faster in capturing the response